Method calculation of thermal characteristics of tubular heatexchange devices - Тарасенко, Олександр Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
On the basis of mathematical modeling the method of calculation of static and dynamic characteristics of tubular heatexchange devices with the cross scheme of movement of heat-carriers is developed. Comparison of settlement and experimental data is given